Effect of strength training with additional acupuncture on balance, ankle sensation, and isokinetic muscle strength in chronic ankle instability among college students - Chang, Shuwan; Tan, Yajun; Cheng, Liang; Zhou, Liping; Wang, Bingcheng; Liu, Heng (Frontiers in Physiology, 2024)
The effects of the combination of strength training and acupuncture on chronic ankle instability have not been studied. This study examined strength training, combined with acupuncture for their effects on balance ability, ankle motion perception, and muscle strength on chronic ankle instability among college students.Methods: Forty-six chronic ankle instability college students were randomly divided into the experimental group (n = 24, strength training + acupuncture) and control group (n = 22, strength training) for an 8-week intervention.For the results at eight weeks compared with the baseline, experimental group: CAI Tool (CAIT) score, ankle dorsiflexion, plantar flex and eversion peak torque (60°/s) and plantar flex peak torque (180°/s) increased by 13.7%, 39.4%, 13.7%, 14.2% and 12.3%, respectively. Dorsiflexion, plantar flexion, inversion and eversion kinesthetic sensation test angle decreased by 17.4%, 20.6%, 15.0% and 17.2%, respectively. Anterior-posterior and medial lateral displacement, anteriorposterior and medial lateral velocity decreased by 28.9%, 31.6%, 33.3% and 12.4%, respectively. Anterior-posterior and medial lateral displacement, anterior-posterior and medial lateral mean velocity decreased by 28.9%, 31.6%, 33.3% and 12.4%, respectively. Control group: CAIT score and the ankle dorsiflexion peak torque (60°/s) increased by 13.8% and 17.9%, respectively. Inversion kinesthetic sensation test angle decreased by 15.2%, whereas anterior-posterior and medial lateral displacement, and anterior-posterior and medial lateral mean velocity decreased by 17.1%, 29.4%, 12.3% and 16.8%, respectively. 2) For the comparison between the groups after eight weeks, the ankle dorsiflexion and plantar flex peak torque (60°/s) in the experimental group was greater than that in control group. Ankle plantar flex kinesthetic sensation test angle, the anterior-posterior displacement and anterior-posterior mean velocity experimental group were lower than those in control group.: Acupuncture treatment in conjunction with muscle strength training can further improve the balance ability of anterior-posterior, ankle dorsiflexion and plantar flex strength and plantar flex motion perception in chronic ankle instability participants.